2022
DOI: 10.3390/electronics11142150
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of Favorable Propagation on Massive MIMO Channels with Generalized Angle Distributions

Abstract: Massive MIMO obtains the multiuser performance gain based on the favorable propagation (FP) assumption, defined as the mutual orthogonality of different users’ channel vectors. Until now, most of the theoretical analyses of FP are based on uniform angular distributions and only consider the horizontal dimension. However, the real propagation channel contains full dimensions, and the spatial angle varies with the environment. Thus, it remains unknown whether the FP condition holds in real deployment scenarios a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The authors of [15] extended the Fourier model in [12] to a multi-user scenario and derived the lower bound for the spectral efficiency of the system utilizing maximum ratio transmission (MRT) and zero-forcing (ZF) precoding schemes with the separable correlation structure. Assuming the wrapped Gaussian azimuth angle distribution and truncated Laplacian elevation angle distribution with the separable structure, the authors of [23] derived the variance profile for the holographic MIMO channels and analyzed the degree of freedom (DoF). Considering the potential of evanescent waves in near-field holographic communications and assuming the separable structure, the authors of [16] analyzed the ergodic MI and validated the improvement of the DoF by simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [15] extended the Fourier model in [12] to a multi-user scenario and derived the lower bound for the spectral efficiency of the system utilizing maximum ratio transmission (MRT) and zero-forcing (ZF) precoding schemes with the separable correlation structure. Assuming the wrapped Gaussian azimuth angle distribution and truncated Laplacian elevation angle distribution with the separable structure, the authors of [23] derived the variance profile for the holographic MIMO channels and analyzed the degree of freedom (DoF). Considering the potential of evanescent waves in near-field holographic communications and assuming the separable structure, the authors of [16] analyzed the ergodic MI and validated the improvement of the DoF by simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm, in particular, exploits some useful properties of random matrices to perform efficient processing of the signals using linear techniques, delivering performances that are only a fraction smaller than the optimal ones. In particular, it has been demonstrated that the so-called "favorable propagation" conditions [6,7] can occur with a number of terminals K that can be of the order of a third of the number of antennas M at the base station [8]. For these reasons, MaMIMO is considered one of the enabling technologies for current 5G systems.…”
Section: Introductionmentioning
confidence: 99%